PENGETAHUAN DAN DUKUNGAN KELUARGA TENTANG ANEMIA TERHADAP KEPATUHAN IBU HAMIL DALAM MENGKONSUMSI TABLET FE DI WILAYAH KERJA PUSKESMAS BERSERI - Yadriati Maya Pesa (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Abstract: Anemia is still often experienced by pregnant women due to iron deficiency, this happens because most pregnant women do not understand the nutritional needs during pregnancy and compliance is still lacking in consuming iron FE tablets. Anemia in pregnancy is a body condition with hemoglobin levels in the blood <11g% in the 1st and 3rd trimesters or Hb levels <10.5 g% in the 2nd trimester. Fe in the work area of the serial health center. The type of research used is analytic with a cross sectional approach. The research population was 86 respondents and the sample was 46 people. Sampling with purposive sampling technique. data analysis using univariate and bivariate. Based on the Chi Square test, the p-value is 0.00<0.05, which means that knowledge has a relationship with the compliance of pregnant women in consuming Fe tablets, while the results of the analysis of the relationship between family support variables and the compliance of pregnant women in consuming Fe tablets have a p-value of 0.14>0.05. , this means that there is no relationship between family support and maternal compliance in consuming Fe tablets.Keywords: Fe tablets, Iron, Knowledge, Family Support, Obedience of pregnant women.